Enhancing English Language Instruction in Higher Education through the Integration of Critical Thinking Development (Eurasian Research Bulletin, 2025)
In the 21st century, English language education has shifted from emphasizing grammatical accuracy to developing communicative and cognitive competences. Among these, critical thinking is a key component in preparing students for independent learning, informed decision-making, and global citizenship. This paper examines how critical thinking can be effectively integrated into English teaching practices at the higher education level. It discusses theoretical foundations, pedagogical approaches, and organizational strategies that promote critical engagement. The study argues that English language teaching (ELT) should move beyond linguistic mastery to foster reflective, analytical, and evaluative skills that empower students to construct and express reasoned viewpoints.